The influence of impression management on the online presentation of self in young adults in Singapore - Teh, Justin Jia Pin (2014)
Facebook has become the social networking site of choice for young adults in Singapore, boasting high penetration rates. As such, it has overlapped into the offline lives of many people. Hence, young adults see their online identities as an extension of their offline lives. However, the public nature of the internet and Facebook has necessitated the engagement of facework and presentation of self on Facebook in order to avoid the collapse of social context, where friends from different social circles inevitably interact. The influence of impression management in the construction of online identities in young Singaporeans was examined through interviews and content analysis of their Facebook profiles. Results point to impression management playing a role in the online presentation of self, although it was often not done on a conscious level. However, it also suggested that young adults in Singapore still viewed their offline lives as more important despite the interconnectedness of their online and offline lives.